Self-portrait, with parents and footnotes : in and out of a postwar Jewish childhood - Aronowicz, Annette, 1952- (Cherry Orchard Books, imprint of Academic Studies Press, 2021)
"Self-Portrait, with Parents and Footnotes is a story of movement. Moving from city to city characterized the author's growing up-from Poland to Belgium and from the East Coast to the West Coast of the United States. The book also moves between past and present. The authors' parents, Jews from Eastern Europe, lived through the Spanish Civil War, the Second World War, the post-war Communist world, and much migration in between. How were these events transmitted to their child, and what questions do they give rise to today? The book moves between straightforward story-telling and reflections on memory, on politics and religion, and on literature. It seeks the genesis of intellectual interests in personal history"--